Who Is Dermanyssus gallinae? Genetic Structure of Populations and Critical Synthesis of the Current Knowledge - Roy, Lise; Giangaspero, Annunziata; Sleeckx, Nathalie; Øines, Øivind (Frontiers in Veterinary Science, 2021)
In spite of the economic and animal welfare importance of the Poultry Red Mite Dermanyssus gallinae, its genetic structure has been studied in a scattered way so far. The prophylaxis and control of such a globally distributed ectoparasite can be significantly improved by understanding its genetic population structure (composition in species and intraspecific variants). The present study aims to establish a rigorous framework for characterizing the neutral genetic structure of D. gallinae based on a literature review combined with an integrative analysis of the data available in GenBank on population-level nucleotide sequence diversity supplemented by a new dataset. The integrative analysis was conducted on sequence data extracted from GenBank coupled with new sequences of two fragments of the mitochondrial gene encoding Cytochrome Oxidase I (CO1) as well as of an intron of the nuclear gene encoding Tropomyosin (Tpm) from several PRM populations sampled from European poultry farms. Emphasis was placed on the use of the mitochondrial gene encoding CO1 on which the main universal region of DNA barcoding in animals is located. The species D. gallinae sensu lato is a species complex, encompassing at least two cryptic species, i.e., not distinguishable by morphological characters: D. gallinae sensu stricto and D. gallinae L1. Only D. gallinae s.s. has been recorded among the populations sampled in poultry farms worldwide. Current knowledge suggests they are structured in three mitochondrial groups (haplogroups A, B and C). Haplogroup A is totally cosmopolitan and the other two present slightly contrasted distributions (B rather in the northern part of Europe, C more frequently found in the southern part). Recent data indicate that a dynamic geographic expansion of haplogroup C is underway in Europe. Our results also show that NUMT (nuclear mitochondrial DNA) pseudogenes have generated artifactual groups (haplogroups E and F). It is important to exclude these artifact groups from future analyses to avoid confusion. We provide an operational framework that will promote consistency in the analysis of subsequent results using the CO1 fragment along with recommendations for future analyses.